Interview: Ethics and law continue to shape psychiatric practice and research. (October 2013) - Appelbaum, Paul S
Paul S Appelbaum is the Elizabeth K Dollard Professor of Psychiatry, Medicine and Law, Director of the Division of Law, Ethics and Psychiatry, Department of Psychiatry (College of Physicians and Surgeons of Columbia University, NY, USA), a research psychiatrist at the New York State Psychiatric Institute (NY, USA) and an affiliated faculty member at Columbia Law School (NY, USA). He directs Columbia University's Center for Research on Ethical, Legal and Social Implications of Psychiatric, Neurologic and Behavioral Genetics, and heads the Clinical Research Ethics Core for Columbia University's Clinical and Translational Science Award program. Appelbaum was previously the AF Zeleznik Distinguished Professor of Psychiatry, Chairman of the Department of Psychiatry, and Director of the Law and Psychiatry Program at the University of Massachusetts Medical School (MA, USA). He is the author of many articles and books on law and ethics in clinical practice and research, including four that were awarded the Manfred S Guttmacher Award from the American Psychiatric Association (APA) and American Academy of Psychiatry and Law. Appelbaum is a past president of the APA, American Academy of Psychiatry and Law, and Massachusetts Psychiatric Society. He has served twice as chair of the APA Council on Psychiatry and Law, now chairs the APA Committee on Judicial Action, and was a member of the MacArthur Foundation Research Networks on Mental Health and the Law, and on Mandatory Outpatient Treatment. Appelbaum has received the APA's Isaac Ray Award for 'outstanding contributions to forensic psychiatry and the psychiatric aspects of jurisprudence', was the Fritz Redlich Fellow at the Center for Advanced Study in the Behavioral Sciences (CA, USA) and has been elected to the Institute of Medicine of the National Academy of Sciences. Appelbaum graduated from Columbia College (NY, USA), received his Doctorate in Medicine from Harvard Medical School (MA, USA) and completed his residency in psychiatry at the Massachusetts Mental Health Center (MA, USA)/Harvard Medical School in Boston.